RENDAHNYA MINAT AKSEPTOR KB MENGGUNAKAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI POSYANDU MELATI II WILAYAH KERJA PUSKESMAS RENGASDENGKLOK : RENDAHNYA MINAT AKSEPTOR KB MENGGUNAKAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI POSYANDU MELATI II WILAYAH KERJA PUSKESMAS RENGASDENGKLOK - Riska Setiawati Setiawati; Irma Yanti; Nelly Apriningrum (HSG (Health Science Growth) Journal, 2023)
The purpose of this study was to determine the factors that influence the low interest of mothers in the use of intrauterine devices (IUD). Interest in the IUD is still low because there are many perceptions that cause negative sides. The research design used a cross sectional approach. The sampling technique using Accidental Sampling amounted to 47 respondents. Data analysis was performed using chi-square. Data processing with SPSS. The results of the study the p-value = 0.19 means that there is a relationship between education and interest in using, p-value = 0.06 means there is a parity relationship with interest in using, p-value = 0.619 means there is no relationship between age and interest in using, p -value = 0.099 means there is no relationship between information sources and interest in using, p-value = 0.143 means there is no relationship between information sources and interest in using. The conclusion from each variable of education, parity, age, source of information and perception, which has a relationship with mother's interest in using is education and parity. The hope from the results of this study is to eliminate negative perceptions about the use of contraceptives by being approached by the relevant officers, especially health workers